Mediators of acceptance and mindfulness-based therapies for anxiety and depression: A systematic review and meta-analysis - Johannsen, Maja; Nissen, Eva Rames; Lundorff, Marie; O'Toole, Mia Skytte (Clinical psychology review, 2022)
Acceptance and mindfulness-based therapies have shown efficacy in the treatment of anxiety and depression. Arguably, acceptance and mindfulness-based therapies target core processes in anxiety and depression by increasing mindful attention, decentering, and acceptance. The present study identified randomized controlled trials of acceptance and mindfulness-based therapies for anxiety and depression. Specifically, we aimed to synthesize the indirect effect of the three putative mediators (i.e., mindful attention, decentering, acceptance) on anxiety and depression. Electronic searches yielded 4989 unique records, which were screened for eligibility by two independent raters, resulting in the identification of 33 eligible studies (30 independent trials). The overall pooled mediating effect of mindful attention, decentering, and acceptance was small to medium (r = 0.145, p < .001). Type of mediation analysis emerged as the only statistically significant moderator. Specifically, studies using correlation-based mediation approaches showed statistically significant mediating effects, while studies using causal time-lag analyses did not yield statistically significant mediating effects. Mediator specificity could not be established. In conclusion, putative mediators of acceptance and mindfulness-based therapies mediated treatment effects on anxiety and depression. Limitations in study number, designs, and statistical approaches employed restrict conclusions regarding specificity and causality. •Mediators of acceptance and mindfulness-based therapies for anxiety and depression were examined in 33 studies.•Mindful attention, decentering, and acceptance were significant mediators of acceptance and mindfulness-based therapies.•The overall effect size found was small-to-medium and generally robust.•Study designs preclude conclusions on mediator specificity and temporal precedence.